2018
DOI: 10.3390/nu10040424
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Isoflavone Supplementation Plus Combined Exercise on Lipid Levels, and Inflammatory and Oxidative Stress Markers in Postmenopausal Women

Abstract: This study tested the effect of isoflavone supplementation in addition to combined exercise training on plasma lipid levels, inflammatory markers and oxidative stress in postmenopausal women. Thirty-two healthy and non-obese postmenopausal women without hormone therapy were randomly assigned to exercise + placebo (PLA; n = 15) or exercise + isoflavone supplementation (ISO; n = 17) groups. They performed 30 sessions of combined exercises (aerobic plus resistance) over ten weeks and consumed 100 mg of isoflavone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
3
46
0
2
Order By: Relevance
“…Isoflavones are a group of secondary metabolites found in soybean, which play a key role in lowering cholesterol levels and preventing cancer, osteoporosis, and cardiovascular disease [26][27][28]. Therefore, the total isoflavone content is an important food quality determinant of soybean products.…”
Section: Influence Of Paw On Total Isoflavone Contentmentioning
confidence: 99%
“…Isoflavones are a group of secondary metabolites found in soybean, which play a key role in lowering cholesterol levels and preventing cancer, osteoporosis, and cardiovascular disease [26][27][28]. Therefore, the total isoflavone content is an important food quality determinant of soybean products.…”
Section: Influence Of Paw On Total Isoflavone Contentmentioning
confidence: 99%
“…(29) The efficiency of TBARS inhibition may depend on the individual isoflavones concentration in the extract, with some compounds having low or moderate efficiency to inhibit TBARS, (46) which may explain the slight interaction observed in this study (p = 0.037), and also why other studies found no changes in lipid peroxidation markers with ISO. (32,33) One of the main benefits from exercise training is related to improvements in antioxidant defense. In this way, we found an increase in SOD in both groups after combined exercise training indicating that this type of exercise training, independently of ISO, can improve the antioxidant activity of this enzyme in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training was performed as previously described. (32) Briefly, the exercise training consisted of 30 sessions of combined aerobic and resistance exercises during the same session. Exercise sessions took place three times per week on non-consecutive days, over 10 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations